Guided-mode resonant narrowband terahertz filtering by periodic metallic stripe and patch arrays on cyclo-olefin substrates. Issue 1 (December 2018) - Ferraro, Antonio; Zografopoulos, Dimitrios; Caputo, Roberto; Beccherelli, Romeo
Abstract We experimentally and theoretically demonstrate a class of narrowband transmissive filters in the terahertz spectrum. Their operation is based on the excitation of guided-mode resonances in thin films of the low-loss cyclo-olefin polymer Zeonor, upon which aluminum stripe and patch arrays are patterned via standard photolithography. The filters are engineered to operate in low atmospheric loss THz spectral windows, they exhibit very high transmittance and quality factors, compact thickness, and mechanical stability. The dependence of their filtering properties on the geometrical parameters, the substrate thickness and the angle of incidence is investigated, discussing the physical limitations in their performance. This class of filters provides a cost-effective solution for broadband source or channel filtering in view of emerging terahertz wireless communication systems.